2019
DOI: 10.3390/polym11030415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Montmorillonite on the Preparation and Properties of Cellulose Aerogels

Abstract: In this study, first, a green and efficient NaOH/urea aqueous solution system was used to dissolve cellulose. Second, the resulting solution was mixed with sodium montmorillonite. Third, a cellulose/montmorillonite aerogel with a three-dimensional porous structure was prepared via a sol-gel process, solvent exchange and freeze-drying. The viscoelastic analysis results showed that the addition of montmorillonite accelerated the sol-gel process in the cellulose solution. During this process, montmorillonite adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…It could be seen from Figure 13b and 13c that the adsorption rate of n-MCPMA was slower than that of d-MCPMA, which might be due to the disordered arrangement of pore structure, resulting in the uneven oil absorption process and the slow adsorption rate. Carbon aerogel 140 14-26 [48] NFC/PVA/SAC 159 35-85 [49] Cotton cellulose aerogel 154 20-42 [50] Chitosan/Cellulose aerogel 152 14-28 [51] Sodium alginate/CNF 148 34 [52] Graphene/cellulose/silica 157 39-68 [53] NFC/OA/Fe 3 O 4 84 68 [54] TMCs/CNT/CMC 148 28 [55] Poly(lactic acid) foam 151 32 [56] Bamboo fibre aerogel 132 7-11 [57] Cellulose/montmorillonite No 4-7 [40] CNF/PVA/MMT 140 This work RONG ET AL.…”
Section: Hydrophobic Lipophilic and Absorption Capacitymentioning
confidence: 99%
“…It could be seen from Figure 13b and 13c that the adsorption rate of n-MCPMA was slower than that of d-MCPMA, which might be due to the disordered arrangement of pore structure, resulting in the uneven oil absorption process and the slow adsorption rate. Carbon aerogel 140 14-26 [48] NFC/PVA/SAC 159 35-85 [49] Cotton cellulose aerogel 154 20-42 [50] Chitosan/Cellulose aerogel 152 14-28 [51] Sodium alginate/CNF 148 34 [52] Graphene/cellulose/silica 157 39-68 [53] NFC/OA/Fe 3 O 4 84 68 [54] TMCs/CNT/CMC 148 28 [55] Poly(lactic acid) foam 151 32 [56] Bamboo fibre aerogel 132 7-11 [57] Cellulose/montmorillonite No 4-7 [40] CNF/PVA/MMT 140 This work RONG ET AL.…”
Section: Hydrophobic Lipophilic and Absorption Capacitymentioning
confidence: 99%
“…Compared with the regenerated cellulose aerogel prepared by our previous report, the density of CMC aerogel is significantly reduced. Meanwhile, the compressive modulus is also reduced [26].…”
Section: Resultsmentioning
confidence: 99%
“…They obtained a sorption ratio of 7.97-10.63 g/g for vacuum pump oil and 8.98-11.44 g/g for linseed oil, and the highest results were presented by the samples with a medium starch concentration [6]. Long et al (2019) synthesized cellulose aerogels with sodium montmorillonite, and showed a sorption capacity between 4.5 g/g and 6 g/g for #48 and #220 lubricating oil [7]. Wang et al (2019) used hydrophobic alginate-based foams induced by zirconium ions for oil and organic solvents cleanup, and obtained a sorption capacity of 3.3-28.9 g/g [8].…”
Section: Removal Of Heavy Oil From Connate/deionized/seawater Mixturementioning
confidence: 99%